My apron : a story from my childhood - Carle, Eric. (New York : Philomel Books, 1994)
After his aunt makes him an apron just like his uncle's, a young boy helps him plaster the chimney.
"Includes a cloth apron."
"Ages 5 and up"--Cover p. [4].
Keywords: Plastering -- Juvenile fiction; Uncles -- Juvenile fiction; Aprons -- Juvenile fiction